Properties of Calcium Sulfoaluminate Cement Mortar Modified by Hydroxyethyl Methyl Celluloses with Different Degrees of Substitution - Shaokang Zhang (Molecules, 2021)
This paper studies the influence of hydroxyethyl methyl cellulose (HEMC) on the properties of calcium sulfoaluminate (CSA) cement mortar. In order to explore the applicability of different HEMCs in CSA cement mortars, HEMCs with higher and lower molar substitution (MS)/degree of substitution (DS) and polyacrylamide (PAAm) modification were used. At the same time, two kinds of CSA cements with different contents of ye’elimite were selected. Properties of cement mortar in fresh and hardened states were investigated, including the fluidity, consistency and water-retention rate of fresh mortar and the compressive strength, flexural strength, tensile bond strength and dry shrinkage rate of hardened mortar. The porosity and pore size distribution were also analyzed by mercury intrusion porosimetry (MIP). Results show that HEMCs improve the fresh state properties and tensile bond strength of both types of CSA cement mortars. However, the compressive strength of CSA cement mortars is greatly decreased by the addition of HEMCs, and the flexural strength is decreased slightly. The MIP measurement shows that HEMCs increase the amount of micron-level pores and the porosity. The HEMCs with different MS/DS have different effects on the improvement of tensile bond strength in different CSA cement mortars. PAAm modification can improve the tensile bond strength of HEMC-modified CSA cement mortar.